Percepções de professoras e professores sobre a violência que viveram na família e na escola: analisando a violência da escola - Silva, Adriele Gonçalves da [UNESP] (2015)
The objective of this research is to verify if teachers suffered violence during their childhood and adolescence, either in the family environment or at school, aiming to open a reflection about the production of school violence, overall, the one committed by teachers against their students. This investigation is one stage of a research called Exposição de professores à violência na infância e juventude: analisando reflexos dessa exposição na produção da cultura da violência em espaço escolar, sponsored by Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP), process number 2013/25836 - 4. It consists in an exploratory search whose result has hybrid nature: fundamental and enlargement of the empirical basis about the problematic violence in the school space. The approach is quantitative and qualitative. The sources are seven interviews, semi-structured, executed with three female teachers and four male teachers, who work in the Elementary School - Cycle I and II, in a public state school, located in Araraquara - São Paulo. Interviews were conducted with the support of the method of oral history (THOMPSON, 1992), whose main ally memory. The analysis of the data was done through an inflection of the technique Content Analysis (BARDIN, 1977). The grounding was organized from dissertations and thesis made from 2008 to 2012, in Education post-graduation programs in Brazil, about violence in the school space. In this group of sources, stand out 10 studies that use as a category of analysis types of violence in the school space described by Charlot (2002, 2005): violence at school, violence to the school and violence of the school. In addition, authors who are dedicated to the study of violence also served as a foundation for our research, including: Abramovay (2005), Bourdieu (2010a, 2010b), Buoro et al (1999), Cardia (2012), Debarbieux (2001, 2002a, 2002b), Michaud (1989), Santos (2009), Sposito (2001), ...